2018
DOI: 10.3758/s13421-018-0840-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluency misattribution and auditory hindsight bias

Abstract: We conducted three experiments to test the fluency-misattribution account of auditory hindsight bias. According to this account, prior exposure to a clearly presented auditory stimulus produces fluent (improved) processing of a distorted version of that stimulus, which results in participants mistakenly rating that item as easy to identify. In all experiments, participants in an exposure phase heard clearly spoken words zero, one, three, or six times. In the test phase, we examined auditory hindsight bias by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Much debate exists over the specific cognitive mechanism that mediates the bias (e.g., Bernstein, Kumar, Masson, & Levitin, 2018; Pezzo, 2003, Pohl, 1998; Pohl, Bayen, Arnold, Auer, & Martin, 2018; Wasserman et al, 1991). We believe that the instances that do not result in the curse of knowledge are as theoretically informative (if not more informative) than instances that result in the curse of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Much debate exists over the specific cognitive mechanism that mediates the bias (e.g., Bernstein, Kumar, Masson, & Levitin, 2018; Pezzo, 2003, Pohl, 1998; Pohl, Bayen, Arnold, Auer, & Martin, 2018; Wasserman et al, 1991). We believe that the instances that do not result in the curse of knowledge are as theoretically informative (if not more informative) than instances that result in the curse of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also proposed fluency misattribution as a mechanism that contributes to the curse of knowledge. Researchers suggest that when information feels fluent (i.e., easy to process, easy to recall, or easy to integrate with our existing knowledge structures), we tend to think that this information is obvious to others (Bernstein et al, 2018; Birch et al, 2017; Harley et al, 2004). In other words, we misattribute the subjective ease associated with a piece of information to its objective ease, or foreseeability, to others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only do individuals believe that their perspective-taking is shared with others as reflected in the commonality of hindsight knowledge (Bernstein et al, 2018 ; Birch et al, 2017 ; Higham et al, 2017 ; Hoch & Loewenstein, 1989 ; Wood, 1978 ); they can overestimate it. Demonstrating the salience and influence of correct answers, Birch et al ( 2017 ) found participants who knew the correct answers overestimated the percentage of peers naïve to the answers who would answer correctly.…”
Section: Introductionmentioning
confidence: 99%